Folliculitis Decalvans: A Review of Current Treatment Modalities - Krzesłowska, Wiktoria Julia; Szewczyk, Kamila; Pytel, Paulina; Szewczyk, Bartłomiej; Wiśniewski, Szymon; Hołownia, Weronika (Journal of Education, Health and Sport, 2024)
Background: Folliculitis decalvans (FD) is a rare subtype of neutrophilic cicatricial alopecia, firstly described by Quinquad in 1888, as inflammatory scalp disease usually affecting young adults. The exact etiopathology of the disease is not fully understood, however the presence of Staphylococcus aureus, dysfunction of the host’s immune response, genetic factors, previous trauma of the scalp, as well as Epidermal Growth Factor Receptor inhibitors (EGFRi) use seem to play a role. Clinically, FD presents with scarring alopecic patches with follicular pustules, crusts and tufted hair. Objectives: As the full etiology of the disease is unknown and most data in the literature is based on retrospective date, therapeutic management is not precisely established. The objective of this review is to describe therapeutic options, as well as highlighting potential new therapeutic modalities reported in the literature. Limitations: Because FD is a rare disease, the main limitation is lack of randomized control trials, evaluating therapeutic modalities. Methods: An exhaustive search of references related to FD published in PubMed between 2017 and 2024 was undertaken, using the search term: "folliculitis decalvans". Articles with large patient cohorts and reviews were included, as well as case reports and case series, that reported novel treatment approaches for FD. Conclusions: The management of FD poses a challenge. Systemic antibiotics, particularly rifampicin and clindamycin, are considered the first-line agents and are commonly used in combination with local therapies. Systemic isotretinoin yields sustained remission in some cases, while biological agents exhibit promise in managing severe FD. Novel therapeutic modalities, incorporating, among others, botulinum toxin A injections, Platelet-Rich-Plasma (PRP), or surgical procedures, necessitate randomized double-blind trials to evaluate their safety and efficacy.